On the relationship between aging, edical progress and age-specific health care expenditures - Walter Ried (Universität Greifswald, Rechts- und Staatswissenschaftliche Fakultät, 2007)
This paper investigates the impact of population aging, driven by medical progress, upon agespecific expenditure on health care. In a model set up in discrete time, individuals at each age may catch a lethal disease which, upon receiving appropriate medical treatment, nevertheless involves a mortality risk such that length of life is stochastic. The incidence of lethal diseases, the associated survival probability conditional upon treatment, and health care expenditure conditional upon health status may all depend on an individuals history. For a given age, the history of an individual contains information on her health status in the past. Medical progress is taken to involve an increase in the survival probability of a specified lethal disease. On the one hand, this produces a direct effect on age-specific health care expenditure to the extent that progress affects the cost of treatment of the disease. On the other hand, indirect effects may also arise. These effects are caused by individuals who, having survived the disease at some prior age due to progress, change the structure of individuals alive at current age. Specifically, the "new survivors" may have an influence on age-specific expenditure either through changes in the incidence of lethal diseases or in the associated treatment cost. The sign of an indirect effect crucially depends on health care expenditure for "new survivors" relative to their peers. The analysis yields a number of general results which are important for the discussion of the impact of medical progress on the age profile of health care expenditure. Compression of morbidity, to the extent that it involves a reduction in age-specific expenditure, is neither necessary nor sufficient for medical progress to produce a downward shift of the profile. A similar observation applies to an expansion of morbidity. Both concepts relate to "new survivors" and, thus, take into account only indirect effects of progress.
Keywords: I12; J11; O33; 330; aging; medical progress; age-specific expenditure on health care; Gesundheitskosten; Alternde Bevölkerung; Technischer Fortschritt; Pharmazeutisches Produkt; Medizinisches Produkt; Theorie